DNA barcoding of 19 Lutjanus species to support fisheries management in the Bird’s Head Seascape, Papua, Indonesia - ABDUL HAMID A. TOHA; EMMANUEL MANANGKALANGI; BAYU PRANATA; MUHAMMAD DAILAMI; ANTAJALA R. MAULANA; DESTIA F. ARIYANI; MARTHIN D. T. GRATIA; RAKHMAD N. PRATAMA; SHINTA E. NURCAHYANI; SINDI MILANSAR; JENI JENI; RADWA F. H. PUTRI; ZETH PARINDING; ESIE M. WANGI; ANDI FAJERIANI WYRASTI; CORAZON E. M. P. MAYOR (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Toha AHA, Manangkalangi E, Pranata B, Dailami M, Maulana AR, Ariyani DF, Gratia MDT, Pratama RN, Nurcahyani SE, Milansari S, Jeni, Putri RFH, Parinding Z, Wangi EM, Wyrasti AF, Mayor CEMP. 2025. DNA barcoding of 19 Lutjanus species to support fisheries management in the Bird’s Head Seascape, Papua, Indonesia. Biodiversitas 26: 5287-5302. Red snapper species (family Lutjanidae) are economically important reef fishes traded at local, national, and international levels. However, species-level taxonomic resolution and conservation assessments remain limited in the Bird’s Head Seascape (BHS) region of West Papua, Indonesia. This study applied DNA barcoding of the mitochondrial cytochrome C Oxidase subunit I (COI) gene to assess Lutjanus species diversity and distribution within the Kaimana and Fakfak Marine Protected Areas (MPAs). A total of 77 specimens were successfully sequenced, resulting in a barcoding success rate of 100%. Nineteen species were identified: Lutjanus argentimaculatus, L. bengalensis, L. biguttatus, L. bohar, L. decussatus, L. ehrenbergii, L. erythropterus, L. fulviflamma, L. fulvus, L. gibbus, L. quinquelineatus, L. lemniscatus, L. malabaricus, L. monostigma, L. rufolineatus, L. russellii, L. sebae, L. timoriensis, and L. vitta. Thirteen species were recorded in Fakfak and twelve in Kaimana, with several species unique to each MPA. No genetic differences were observed among individuals within the same species. In contrast, the genetic distance between different species ranged from 2.8% to 19.3%. A total of nineteen monophyletic groups were recovered in the NJ phylogenetic trees, which were supported by high bootstrap values (91-100%). Lutjanus decussatus formed two subgroups in the phylogenetic trees. All identified species are currently listed as Least Concern (LC) by the IUCN, though population trends for most remain unknown, and some are declining. These findings demonstrate the utility of DNA barcoding for accurate species identification in data-poor tropical regions and provide a genetic baseline for future monitoring efforts. The confirmed presence of commercially exploited and potentially declining species underscores the need for site-specific fishery assessments and adaptive management strategies. Integrating molecular tools into routine monitoring can enhance enforcement of species-based catch limits and support sustainable fisheries management within Indonesia’s MPAs.